2017
DOI: 10.18535/jmscr/v5i5.159
|View full text |Cite
|
Sign up to set email alerts
|

Using Various Types of Lethal Ovitrap to Control Aedes sp in Endemic Dengue Hemorrhagic Fever (DHF)

Abstract: Introduction: Dengue Hemorrhagic Fever (DHF) every year always strikes all districts in Indonesia which

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…It is also in line with research that shows a tendency for mosquitoes to prefer laying eggs in black containers compared to other colors (41). Likewise, research conducted in the Banyumas region shows that Aedes albopictus prefer black plastic bottles or cups to other materials (23).…”
Section: Ovitrap Color Modification and Ovitrap Trap Abilitysupporting
confidence: 85%
See 1 more Smart Citation
“…It is also in line with research that shows a tendency for mosquitoes to prefer laying eggs in black containers compared to other colors (41). Likewise, research conducted in the Banyumas region shows that Aedes albopictus prefer black plastic bottles or cups to other materials (23).…”
Section: Ovitrap Color Modification and Ovitrap Trap Abilitysupporting
confidence: 85%
“…In this study, plastic ovitrap was used because different research results indicated that plastic is the most common container material used by the community and has high potential as a place for mosquito breeding (23)(24). The slightly rough plastic surface allows mosquitoes to be well-positioned to lay eggs.…”
Section: The Trend Of Eggs Trapped In Ovitrapmentioning
confidence: 99%
“…Although not statistically supported, field tests conducted in Semarang and Salatiga (Indonesia) using lethal ovitraps revealed a decrease in Ae. aegypti population density [ 26 , 27 ]. According to a field study, lethal ovitrap control programs significantly impacted Ae.…”
Section: Mechanical Methodsmentioning
confidence: 99%